Blood lactate clearance during active recovery after an intense running bout depends on the intensity of the active recovery - Menzies, P.; Menzies, C.; McIntyre, L.; Paterson, P.; Wilson, J.; Kemi, O. J. (Journal of Sports Sciences, 2010)
High-intensity exercise training contributes to the production and accumulation of blood lactate, which is cleared by active recovery. However, there is no commonly agreed intensity or mode for clearing accumulated blood lactate. We studied clearance of accumulated blood lactate during recovery at various exercise intensities at or below the lactate threshold after high-intensity interval runs that prompted lactate accumulation. Ten males repeated 5-min running bouts at 90% of maximal oxygen uptake (VO2max), which increased blood lactate concentration from 1.0 ± 0.1 to 3.9 ± 0.3 mmol/l. This was followed by recovery exercises ranging from 0 to 100% of lactate threshold. Repeated blood lactate measurements showed faster clearance of lactate during active versus passive recovery, and that the decrease in lactate was more rapid during higher (60-100% of lactate threshold) than lower (0-40% of lactate threshold) (P < 0.05) intensities. The more detailed curve and rate analyses showed that active recovery at 80-100% of lactate threshold had shorter time constants for 67% lactate clearance and higher peak clearance rates than 40% of lactate threshold or passive recovery (P < 0.05). Finally, examination of self-regulated intensities showed enhanced lactate clearance during higher versus lower intensities, further validating the intensity dependence of clearance of accumulated blood lactate. Therefore, active recovery after strenuous exercise clears accumulated blood lactate faster than passive recovery in an intensity-dependent manner. Maximum clearance occurred at active recovery close to the lactate threshold.